Which inflation to target? A small open economy with sticky wages indexed to past inflation - Alessia Campolmi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
In a closed economy context there is common agreement on price inflation stabilization being one of the objects of monetary policy. Moving to an open economy context gives rise to the coexistence of two measures of inflation: domestic inflation (DI) and consumer price inflation (CPI). Which one of the two measures should be the target variable? This is the question addressed in this paper. In particular, I use a small open economy model to show that once sticky wages indexed to past CPI inflation are introduced, a complete inward looking monetary policy is no more optimal. I first, derive a loss function from a second order approximation of the utility function and then, I compute the fully optimal monetary policy under commitment. Then, I use the optimal monetary policy as a benchmark to compare the performance of different monetary policy rules. The main result is that once a positive degree of indexation is introduced in the model the rule performing better (among the Taylor type rules considered) is the one targeting wage inflation and CPI inflation. Moreover this rule delivers results very close to the one obtained under the fully optimal monetary policy with commitment.
Keywords: 330; Inflationsbekämpfung; Geldpolitisches Ziel; Kleine offene Volkswirtschaft; Lohnrigidität; Indexbindung; Theorie